Development of a wheat single gene FISH map for analyzing homoeologous relationship and chromosomal rearrangements within the Triticeae - Danilova, Tatiana V.; Friebe, Bernd R.; Gill, Bikram S. (My University, 2014)
To transfer agronomically important genes from wild relatives to bread wheat (Triticum aestivum L., 2n = 6x = 42, AABBDD) by induced homoeologous recombination, it is important to know the chromosomal relationships of the species involved. Fluorescence in situ hybridization (FISH) can be used to study chromosome structure. The genomes of allohexaploid bread wheat and other species from the Triticeae tribe are colinear to some extent, i.e., composed of homoeoloci at similar positions along the chromosomes, and with genic regions being highly conserved. To develop cytogenetic markers specific for genic regions of wheat homoeologs, we selected more than 60 full-length wheat cDNAs using BLAST against mapped expressed sequence tags and used them as FISH probes. Most probes produced signals on all three homoeologous chromosomes at the expected positions. We developed a wheat physical map with several cDNA markers located on each of the 14 homoeologous chromosome arms. The FISH markers confirmed chromosome rearrangements within wheat genomes and were successfully used to study chromosome structure and homoeology in wild Triticeae species. FISH analysis detected 1U-6U chromosome translocation in the genome of Aegilops umbellulata, showed colinearity between chromosome A of Ae. caudata and group-1 wheat chromosomes, and between chromosome arm 7S#3L of Thinopyrum intermedium and the long arm of the group-7 wheat chromosomes.
Citation: Danilova, T., . . . & Gill, B. (2014). Development of a wheat single gene FISH map for analyzing homoeologous relationship and chromosomal rearrangements within the Triticeae. Theoretical and Applied Genetics, 127(3), 715-730. https://doi.org/10.1007/s00122-013-2253-z
Keywords: Wheat; Triticeae; Chromosomal rearrangements; Fluorescence in situ hybridization